A comparison of hydrostatic reduction in children with intussusception versus surgery: Single-centre experience - Mohamed El-sayed Eraki (Wolters Kluwer Medknow Publications, 2017)
Background: Intussusception is the most common cause of bowel obstruction in infancy and childhood. Early diagnosis and effective management have reduced its morbidity and mortality in developed countries. Non-surgical reduction remains the first-line treatment of choice for intussusception. The major complication of air enema reduction is bowel perforation and portal venous gas. In recent years, several techniques have been recommended for intussusception treatment. In this study, an evaluation was made of intussusception cases that presented at our clinic and had reduction applied together with saline under ultrasonography and cases, which were surgically treated. Our aim of this study is to evaluate the results of hydrostatic reduction under ultrasound guided and to compare the results with patients treated by surgery for the management of intussusception. Patients and Methods: A retrospective study was done of the records of 100 cases treated for a diagnosis of intussusception between April 2011 and April 2013, in Department of Paediatric Surgery, Zagazig University Hospital. Patients were evaluated demographics, clinical presentation and management strategy, during the hospitalisation and outcome. Results: This study includes 100 patients diagnosed with intussusception, sixty males and forty females, the age ranged between 1 month and 7 years old. Ultrasound was applied for all patients as a part of diagnosis. Hydrostatic reduction under ultrasound guide was applied to fifty patients, successful hydrostatic reduction was seen in thirty patients and unsuccessful hydrostatic reduction was seen in twenty patients which admitted for surgery, we did not do another chance of hydrostatic reduction for unsuccessful patients, open surgery was done for seventy patients, during surgery, we found ileocolic intussusception in forty patients, ileoileal in twenty patients and colocolic intussusception in ten patients. Leading point of intussusception was seen in 22 patients, Meckel's diverticulum in ten patients, polyp in five patients and lymphoma in seven patients. Manual reduction was done in forty patients and resection anastomosis was done in thirty patients. No mortality in any case. Conclusion: Ultrasound-guided hydrostatic reduction of intussusception is a safe technique which reduces the duration of hospitalisation and treatment costs.